2017
DOI: 10.1371/journal.pone.0172204
|View full text |Cite
|
Sign up to set email alerts
|

The cost of dementia in an unequal country: The case of Chile

Abstract: We study the economic cost of dementia in Chile, and its variation according to socioeconomic status (SES). We use primary data from a survey of 330 informal primary caregivers who completed both a RUD-Lite and a socio-demographic questionnaire to evaluate the severity of dementia and caregiver’s burden. The costs of dementia are broken into three components: direct medical costs (medical care, drugs, tests); direct social costs (social service, daycare); and indirect costs (mostly associated to informal care)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 48 publications
2
48
1
7
Order By: Relevance
“…Formal caregivers are rare in Latin American countries, where family systems are strong. Consistent with previous literature, we found that less than 5% of PWD caregivers were paid professionals . The burden for caregiving lies primarily on family members, and a majority of PWD had one or 2 informal caregivers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Formal caregivers are rare in Latin American countries, where family systems are strong. Consistent with previous literature, we found that less than 5% of PWD caregivers were paid professionals . The burden for caregiving lies primarily on family members, and a majority of PWD had one or 2 informal caregivers.…”
Section: Discussionsupporting
confidence: 89%
“…The relationship between functional ability and unmet needs can be expected, given that people with lower functional ability require more support. An association between low educational level and dementia severity has been previously documented both internationally and in Chile and can be attributed in part to reduced access to formal care . In addition, the number of caregivers was another important variable associated with unmet needs, both regarding ADL and overall needs.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although we valued unpaid care time at minimum wage, the proportion of total costs accounted for by unpaid care would have been even higher had we used a valuation such as national average wage or (taking a replacement cost approach) costs to social care providers of paying home carers for the time. We did not find that unpaid care costs were associated with socioeconomic status, contrary to previous findings [43]. In terms of dementia subtypes and variations in cost, and contrary to the study by Costa et al [44], we found unpaid care costs higher for Parkinson's-type dementia than for Alzheimer's disease participants.…”
Section: Discussioncontrasting
confidence: 99%
“…The monthly cost was USD $690 and USD $1023 for high and low for high socioeconomic status families, respectively. 18 The high percentage of informal care in the total cost of dementia partly stems from the absence of a comprehensive national long-term care program and is consistent with an outdated health system that has failed to provide the complex and multidisciplinary actions that people with chronic diseases require. 7 The need for reform is particularly evident if we consider that WHO estimates a 77% increase in the cases of dementia by 2030 for Chile, Argentina, and Uruguay.…”
Section: Aging In Chile: Some Facts Aging and Health In Chilementioning
confidence: 98%